Controlled traction-a key for safe laparoscopic cholecystectomy - Manangi, Mallikarjuna; Dharini, Dharini; Kumar, Tanvi Sunil; Vishweshwara, Ramya M. (International Surgery Journal, 2021)
Laparoscopic cholecystectomy (LC) is one of the most common laparoscopic procedures performed. The technique of LC has witnessed numerous modifications according to surgeon’s preferences to improve the ergonomics, surgical ease, safety and outcome. Dissection of the gall bladder from the liver bed is one of the troublesome steps. We aim to describe a unique method which is technically easy to perform and provides excellent exposure as well. A total of 206 patients underwent laparoscopic cholecystectomy at our Institute over a year from January 2017 to 2018. The technique of torquing the gallbladder to dissect it off its bed is surgeon friendly with advantages of instrumentation and visualization.